KEMAMPUAN MENGIDENTIFIKASI INFORMASI TEKS DESKRIPSI SISWA KELAS VII SMP - Aprillia Aulia Putri; Erny Harijaty; La Ode Adili (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2024)
The purpose of this study was to describe the ability to identify information in descriptive text for class VII students at SMP Negeri 17 Kendari. The type of research used in this research is field research. The method used in this study is descriptive quantitative, namely describing data quantitatively. The sampling technique in this study was by means of Stratified Propotionate Random Sampling, namely if the elements or groups were not homogeneous, then the sampling was determined based on the low, medium, and high grade strata of the students, then a total of 115 students were obtained. The instrument used in this research is a test in the form of a description. Based on the research results, interpreting the meaning of the word vehicle 74.78%, interpreting the meaning of the word area 79.13%, interpreting the meaning of the word spot 66.08%, interpreting the meaning of the word moment 96.52%, interpreting the meaning of the word exotic 49.65%, answering 20% for pamphlet 2a description, 10.43% for 2b 10.43%, 23.47% for 2c 23.47%, 11.30% for 2d 11.30%, 13.04% for 2e 13.04%, 40% for 2f pamphlet description. Of all the aspects assessed, the aspect of interpreting the meaning of the word moment was ranked the highest with a percentage of 96.52%.